Association between Behavioral Intentions and Knowledge Sharing ; Are Demographics Influential* - Arenawati Sehat, Omar; Shahren, Ahmad Zaidi Adruce (IEEE-SEM Publications, 2019)
Objective: Globally, the inadequate level of knowledge sharing is considered as an increasing concern among educational institutes, impacting educational quality and job performance. Thereby, the study aims to assess the association between behavioral intentions and knowledge sharing by using the Theory of Reasoned Action (TRA). It also examines the influence of the demographic factors on knowledge sharing behavior. Methods: A cross-sectional design was used in this study including a total of 630 academicians from the four educational institutes (Universiti Malaysia Sarawak (UNIMAS), Universiti Teknologi MARA Sarawak, Universiti Putra Malaysia, Bintulu and Politeknik Kuching) based on a survey approach. The collected data were analyzed statistically using PLS SMART- SEM. Results: The results revealed a significant impact of age, gender, work experience, designation, and education on behavioral intentions and knowledge sharing. It also showed a direct association between behavioral intention and knowledge sharing. Conclusion: The study concludes that collaborative practices should be encouraged among academicians for creating a knowledge sharing culture.